INTENSIVE SEPARATE TECHNOLOGY AND ITS INFLUENCE ON THE PROPERTIES OF CEMENT-WATER COMPOSITIONS, SOLUTIONS AND CONCRETES ON THEIR BASIS (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The article reviews the issues related to the mechanical activation of Portland cement in the separate technology of the production of concrete mixtures in the production of concrete and reinforced concrete products. Usually, an essential characteristic of composite building materials based on Portland cement and its varieties used in building processes is their rapid setting of strength. Therefore, scientific researches related to the development of technologies aimed at the intensification of cement hydration processes and the growth of the speed of concrete strength gaining are relevant. The work presents the main technological processes during the production of concrete mixtures using intensive separate technology. The usage of this technology, particularly, makes it possible to significantly increase the reversibility of forms due to a more intense concrete strength gaining on mechanically activated Portland cement, especially during the early stages of hardening. The need to include mineral filler in the form of ground quartz sand during the preparation of the cement-water composition in a high-speed mixer is founded. It was experimentally discovered that the rapid mixing of the cement-water composition in the presence of a C-3 superplasticizer causes a sharp decrease in its effective viscosity, which positively affects the reduction of the water content of concrete mixtures of the required ease of workability.The mechanical activation of Portland cement causes an increase in the amount of chemically bound water in vintage-age cement stone from 13.1% to 17.9%, which means more than 36% compared to the control. It was established that with the same amount of binder, the strength of the concrete on activated Portland cement on the first twenty-four hours of hardening is 1.8...2 times higher compared to the concrete of similar composition, the binder of which was not activated. Over time, the effect of activation on the concrete strength decreases a little, but even at 28 days, the compressive strength of concrete on the activated binder is 25…30% higher compared to the control.
Keywords: concrete; separate technology; tribo-activator; filler; mechanical activation.